Kategori dan Ekspresi Linguistik Wadah Berbahan Dasar Bambu dalam Masyarakat Jawa - Kajian Etnolinguistik - Akhmad Dzukaul Fuad,; Shendy Andrie Wijaya,; Gandung Wirawan, (Jurnal Sosial Humaniora, 2025)
This study aims to describe the form of the lexicon in the Java language (bJ) which has the meaning of bamboo-based container. The description is based on the formation of the lexicon, not necessarily formed and spoken without considering the external aspects of the language (metalanguage) that has existed in the community of speakers. The meta-language that became the starting point and the basis of categorization makes this research not only involves linguistic analysis but a combination of linguistics and anthropology. It is commonly called ethnolinguistic. The lexicon categorization of bamboo-based containers in Javanese is adapted to the form, the domain of use and the meta aspects of the language reflected in each lexicon. It resulted in three domains of use and overall lexicon nouns.